NEW STUDENT RECEPTION SYSTEM DEVELOPED IN LPK PESAT - Reyn Pandapotan Butarbutar; Drs. Sunarto Usna (Jurnal Sistem Informasi, 1997)
Help provide information to monitor student payments, which are needed by allstakeholders, easier data handling so that the desired information will be obtainedquickly and in a manual system is often ignored because the number of data that mustbe addressed.